Correlation of plasma lipid levels and histopathological grading in patients with oral squamous cell carcinoma and its pre-cancerous lesions - Singh, Mohini; Singh, Abhishek Bahadur; Singh, Abhijeet; Agarwal, S. P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Lower levels of lipid in proliferating tissues and in blood compartments may occur due to ongoing process of oncogenesis. The evidence regarding hypolipidemia as a predisposing factor for malignancy is scarce. Therefore, this study was undertaken to study alteration of plasma lipid levels in patients diagnosed with oral squamous cell carcinoma (OSCC) and its oral pre-cancerous (OPC) lesions and also to compare the plasma lipid profile in different grades of OSCC. Methods: A single centre prospective cross sectional study was carried out among 150 consecutive patients of OSCC and OPC lesions. The diagnosis of all lesions was confirmed histopathologically and grading was also done for each lesion based on degree of differentiation and keratinization of tumour cells. Serum total cholesterol, HDL, TG, LDL was estimated by using semi-automated chemical analyzer. The lipid levels were compared by using unpaired t-test between two strata whereas one way analysis of variance (ANOVA) with Tukey’s post-hoc tests was used among more than two strata. Results: Total cholesterol, TG, HDL, and LDL were significantly reduced in OSCC and OPC groups when compared with the reference values. Serum TC, LDL and HDL levels were found to be decreased with the loss of differentiation in histological grading but with no statistical significance. Conclusions: It can be inferred that there is an inverse relationship between the serum lipid profile values of TC, HDLC, TG, LDL and OSCC as well as OPC patients. The lower serum lipid status may be considered a useful indicator for initial changes occurring in neoplastic cells.